2016
DOI: 10.1155/2016/8539127
|View full text |Cite
|
Sign up to set email alerts
|

Adjusting of Wind Input Source Term in WAVEWATCH III Model for the Middle-Sized Water Body on the Basis of the Field Experiment

Abstract: Adjusting of wind input source term in numerical model WAVEWATCH III for the middle-sized water body is reported. For this purpose, the field experiment on Gorky Reservoir is carried out. Surface waves are measured along with the parameters of the airflow. The measurement of wind speed in close proximity to the water surface is performed. On the basis of the experimental results, the parameterization of the drag coefficient depending on the 10 m wind speed is proposed. This parameterization is used in WAVEWATC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Comparison with the measurements at Gorky Reservoir showed that the energy transfer over the wave spectrum in the model was too slow, resulting in a less steep waves than those observed [47]. It is the nonlinear four-wave interactions parametrization DIA that determines the rate of the energy transfer over the wave spectrum.…”
Section: Experiments With Different Wind Input Parameterizationsmentioning
confidence: 92%
See 1 more Smart Citation
“…Comparison with the measurements at Gorky Reservoir showed that the energy transfer over the wave spectrum in the model was too slow, resulting in a less steep waves than those observed [47]. It is the nonlinear four-wave interactions parametrization DIA that determines the rate of the energy transfer over the wave spectrum.…”
Section: Experiments With Different Wind Input Parameterizationsmentioning
confidence: 92%
“…Fetch-limited waves are characterized by more intense wind pumping and stronger non-linearity than is the case in the standard parameterization ST1, which is configured for modeling in the open sea. Therefore, in the second experiment (hereafter-ST1_mod) using the same wind input parameterization, the aerodynamic drag coefficient was changed in accordance with the dependence obtained from field data at Gorky Reservoir [46]:…”
Section: Experiments With Different Wind Input Parameterizationsmentioning
confidence: 99%
“…In addition, numerical simulations on sensitivity are needed because their forecasting performance and accuracy are affected by the spatial and temporal resolution of the model and the wind-wave physics mechanism. In particular, sensitivity numerical simulations for the parameters included in the physics package are performed to optimize the wave model by considering the state of offshore wind input data, topographical characteristics, and grid structure [34][35][36][37]. A wave model's physics package consists of many physical parameters related to wave development parameters, propagation and dissipation, and nonlinear effects by offshore wind.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in different areas of ocean physics rely on statistics of long-term observations. Different methods and instruments are used to do such measurements and collected data might be used, for example, to validate models and to assimilate data in real-time forecasting [1,2].…”
Section: Introductionmentioning
confidence: 99%